Analisis Yuridis Mengenai Tanggung Jawab Notaris Atas Pembuatan Akta Yang Cacat Hukum - Ramdhan, Daddy; Djaja, Benny; Sudirman , Maman (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This study examines the notary’s liability in drafting defective deeds from a juridical perspective, focusing on the normative basis, forms of liability, and resulting legal consequences. As public officials, notaries are mandated to ensure the validity of authentic deeds that carry full evidentiary force. However, in practice, defective deeds—whether due to formal or material defects—still occur, potentially causing losses to the parties involved. This issue is critical since it concerns the principles of legal certainty and the protection of individual rights. The research employs a normative juridical methode with statute, conceptual, and case approaches. Data were obtained through the analysis of legal doctrines, statutory provisions, and relevant court decisions. The findings indicate that notaries may be held liable in three dimensions: civil, criminal, and administrative. Civil liability arises when defective deeds result in losses for one of the parties, while criminal liability applies when a notary commits unlawful acts, such as falsification of identity or documents. Administrative liability relates to violations of the Notary Office Law and professional ethics. The legal consequences of defective deeds include annulment by the court, compensation claims, loss of evidentiary value, and sanctions imposed on the notary. The application of legal certainty theory highlights that defective deeds must be declared null and void to preserve the consistency and stability of the legal system. Meanwhile, the theory of legal protection emphasizes that notary liability serves as a safeguard for the rights of parties harmed by defective deeds. This study contributes theoretically to the development of notarial law and offers practical guidance for notaries to perform their duties with professionalism, prudence, and accountability.